Cathepsin X Cleaves Profilin 1 C-Terminal Tyr139 and Influences Clathrin-Mediated Endocytosis - Pečar Fonović, Urša (PLoS One, 2015)
Cathepsin X, a cysteine carboxypeptidase, is upregulated in several types of cancer. Its molecular target in tumor cells is profilin 1, a known tumor suppressor and regulator of actin cytoskeleton dynamics. Cathepsin X cleaves off the C-terminal Tyr139 of profilin 1, affecting binding of poly-L-proline ligands and, consequently, tumor cell migration and invasion. Profilin 1 with mutations at the C-terminus, transiently expressed in prostate cancer cells PC-3, showed that Tyr139 is important for proper function of profilin 1 as a tumor suppressor. Cleaving off Tyr139 prevents the binding of clathrin, a poly-L-proline ligand involved in endocytosis. More profilin 1—clathrin complexes were present in PC-3 cells when cathepsin X was inhibited by its specific inhibitor AMS36 or silenced by siRNA. As a consequence, the endocytosis of FITC-labeled dextran and transferrin conjugate was significantly increased. These results constitute the first report of the regulation of clathrin-mediated endocytosis in tumor cells through proteolytic processing of profilin 1.